Parallelization of the NASA Goddard Cumulus Ensemble Model for Massively Parallel Computing - Hann-Ming Henry Juang; Wei-Kuo Tao; Xiping Zeng; Chung-Lin Shie; Stephen Lang; Joanne Simpson (Terrestrial, Atmospheric and Oceanic Sciences, 2007)

(untitled)
Massively parallel computing, using a message passing interface (MPI), has been implemented into a three-dimensional version of the Goddard Cumulus Ensemble (GCE) model. The implementation uses the domainresemble concept to design a code structure for both the whole domain and sub-domains after decomposition. Instead of inserting a group of MPI related statements into the model routine, these statements are packed into a single routine. In other words, only a single call statement to the model code is utilized once in a place, thus there is minimal impact on the original code. Therefore, the model is easily modified and/or managed by the model developers and/or users, who have little knowledge of massively parallel computing.